The real-world safety of oseltamivir and baloxavir marboxil in children: a disproportionality analysis of the FDA adverse event reporting system - Wei, Wei; Huang, Liang; Bai, Yingtao; Chang, En; Liu, Jinfeng (Frontiers in Pharmacology, 2024)
Background: Oseltamivir and baloxavir marboxil are the two primary oral drugs approved by the Food and Drug Administration (FDA) for treating influenza. Limited real-world evidence exists on their adverse events in children. The purpose of this study was to explore the adverse event (AE) profiles of oseltamivir and baloxavir marboxil in children based on the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database.Methods: FAERS reports were collected and analyzed from the first quarter of 2019 to the third quarter of 2023. Disproportionality analyses, including the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma Poisson shrinker (MGPS) algorithms, were employed in data mining to quantify the signals of oseltamivir and baloxavir marboxil-related AEs.Results: A total of 464 reports of AEs to oseltamivir as the "primary suspect (PS)" and 429 reports of AEs to baloxavir marboxil as the "PS" were retrieved in pediatric patients. A total of 100 oseltamivirinduced AE signals were detected in 17 system organ classes (SOCs), and 11 baloxavir marboxilinduced AE signals were detected in 6 SOCs after complying with the four algorithms simultaneously. Categorized and summarized by the number of reports of involvement in each SOC, the top 3 for oseltamivir were psychiatric disorders, gastrointestinal disorders, general disorders and site-of-administration conditions, respectively. The top 3 for baloxavir marboxil were injury, poisoning and surgical complications, general disorders and site of administration conditions, and psychiatric disorders, respectively. Conclusion: Our study identifies potential new AE signals for oseltamivir and provides a broader understanding of the safety of oseltamivir and baloxavir marboxil in children.